UMKM Assistance Through Halal Product Certification and Digital Marketing in Pagerngumbuk Village: Pendampingan UMKM Melalui Sertifikasi Produk Halal dan Digital Marketing di Desa Pagerngumbuk - Widhiarto, Maulana Rizky; Solichah, Maulidatus; Biduri, Sarwenda (Procedia of Social Sciences and Humanities, 2022)
The purpose of this community service activity is to provide assistance regarding the use of digital marketing and provide information about the process of licensing the legalization of halal products for UMKM actors in the Pagerngumbuk village. The method we chose to carry out this research activity was to provide knowledge about the importance of using digital technology to market products in the modern era and provide information about the process of legalizing halal products for UMKM actors in the village of Pagerngumbuk. In this study we used descriptive qualitative research methods. This activity was carried out in the form of socialization to the Pagerngumbuk village community about the use of digital technology to market products in the modern era and providing information about the process of legalizing halal products for UMKM actors in the Pagerngumbuk village. With this activity, it is hoped that the Pagerngumbuk village community, especially for UMKM actors, can get knowledge and information about the use of digital technology and the process of legalizing halal products. The results we got after socializing UMKM assistance showed that increasing consumer access to micro-enterprises had an impact on increasing the turnover of UMKM actors. The use of digital technology has created new markets for products and added new creative innovations for UMKM business players.